Development of Inquiry-Based Student Worksheets on Chemical Bonding Material - Das Salirawati; Nur istiqomah (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a type of development research that uses the Four-D development model to produce inquiry-based worksheets on chemical bonding material. This study aims to produce inquiry-based worksheets that are suitable for use in the chemistry learning process. Media quality assessment is based on due diligence by material experts and media experts. The practicality test assessment was carried out by three reviewers and two Peer reviewers, and the readability test was carried out by students. The results of the study were declared feasible with several inputs and suggestions provided by media experts and material experts. The results of the practicality test of inquiry-based worksheets by reviewers and peer reviewers showed a very good category with a total average score of 77.7 and 73.0, respectively. The results of the product readability test by students for all aspects, namely learning, visual display, and software engineering, obtained an average total score of 33.03 out of 9 indicators which were categorized as very good.